Integrasi Enterprise Resource Planning Pada Lini Produksi Menggunakan Internet of Things - Darian Rizaludin; Benediktus Anindito; Slamet Winardi; Moh. Noor Al-Azam (SMARTICS Journal, 2020)
Enterprise Resource Planning the important thing for running business process in company. But along need for automation system connected to the network, integration between Enterprise Resource Planning and the Internet of Things technology is needed. On the production line, automation process needed for the notification system of readiness condition of production machine to help employees who will work can get information related to the condition of machine. The software used for the Enterprise Resource Planning system is open source software, Odoo. In the application of Internet of Things technology, the ESP32 microcontroller will be used as the overall controller of the system installed on the production line machine. Meanwhile, to connect many electronic components such RGB lights, resistors, transistors and power supplies, pcb board will be used to facilitate the stringing of components and reduce cable breakage. In addition to the protocol for sending data from the microcontroller to the server will use the MQTT protocol to publish the subscribe concept, where users will connected the system with network public ip. When the production machine is ready operate, the indicator light will turn green. Then the data will be monitored by supervisors through network that connected to broker MQTT server.